Addressing climate change through stakeholder-centric information systems research: A Scandinavian approach for the masses. (April 2022) - Ågerfalk, Pär J.; Axelsson, Karin; Bergquist, Magnus
Abstract: In this paper, we present three current research projects that explore how digital transformation can be a positive force to help address the causes and mitigate the consequences of climate change. Drawing on the Scandinavian approach to information systems (IS), we advocate a stakeholder-centric approach that can help inform the climate change discourse and assist in developing green digital practices and services. Finally, we propose a research agenda stating that green IS researchers need to engage in co-creative collaborative research and that green IS research should focus on normative design theory, design principles, and actual designs. Highlights: Digital transformation is a positive force to mitigate climate change. A stakeholder-centric IS approach informs discourse and develops green practice. Green IS researchers need to engage in co-creative collaborative research. Green IS should develop normative design theory, design principles, and designs.